Economic Geography of Contagion: A Study on COVID-19 Outbreak in India - Tanika Chakraborty; Anirban Mukherjee (Institute of Labor Economics (IZA), 2021)
We propose a regional inequality-based mechanism to explain the heterogeneity in the spread of Covid-19 and test it using data from India. We argue that a core-periphery economic structure is likely to increase the spread of infection because it involves movement of goods and people across the core and peripheral districts. Using nightlights data to measure regional inequality in the degree of economic activity, we find evidence in support of our hypothesis. Further, we find that regions with higher nightlight inequality also experience higher spread of Covid-19 only when lockdown measures have been relaxed and movement of goods and services are near normal. Our findings imply that policy responses to contain Covid-19 contagion needs to be heterogeneous across India, depending on the ex-ante economic structure of a region.
Keywords: I15; I18; R1; 330; COVID-19; contagion; core-periphery; nightlight; industrial-heterogeneity